Firm age, corporate governance, and capital structure choices - Kieschnick, Robert; Moussawi, Rabih (Journal of Corporate Finance, 2018)
Do the effects of corporate governance on corporate capital structure choices change as a public firm ages? First, we address the direct effects of firm age and governance features on both its decisions to use debt and how much debt to employ. Our analysis reveals a number of novel results. While firm age is positively correlated with the use of debt, it is negatively correlated with how much debt a firm uses. We also find that the effects of firm age on how much debt a firm uses is primarily due to the interaction between firm age and its governance features. The more power that insiders possess, the less debt that the firm uses as it ages. We interpret our evidence as implying that over time, managers allow their risk preferences to dominate their firm capital structure decisions when they are protected from discipline.